The anarchy of living with negativity. Issue 5 (2nd September 2016) - Grassi, Samuele
Abstract: The unanticipated affinities between Lee Edelman's 'politics of negativity' and Saul Neman's theorizations of an 'anti-political politics' of postanarchism allow a re-thinking of the import of queer antisocial projects for a queer politics where 'anarchy' and 'queer' combine. This paper explores a queer anti-political politics of negativity to destabilize the creativity–negativity debate, and to track the emergence of what I call an 'anti-utopian utopianism'. As shown by the 2013 anti-government die-in performance of the Israeli queer anarchist group Mashpritzot, this (im)possible project casts the 'no' of negativity, anarchy and queer as non-essentialist grounds for a politics of difference that insists on the present of dissent as precondition for (its) survival.